Implementation of Collaborative Learning Model to Develop Critical Thinking Character and Learning Initiative in Elementary School Students - Muhammad Arifudin Husin; Widya Utami; Lebie Diefa Salsabila; Ghifar Ghaniyu Rizka; Auliya Aenul Hayati (Jurnal Multidisiplin Sahombu, 2026)
This study discusses the effectiveness of collaborative learning models in shaping elementary students' character, focusing on critical thinking and learning initiative. Employing a mixed methods design, the research involved 30 sixth-grade students at SDN 1 Patalagan, evaluated through classroom observation, teacher interviews, and questionnaires. The results indicate that collaborative learning significantly improves students' critical thinking, teamwork, questioning skills, and argumentation. Students were more active in discussions, providing feedback, and solving problems collaboratively; however, challenges remain regarding low independent learning initiative and information literacy limitations. This research provides empirical evidence for curriculum development and recommendations for strengthening character-based teaching in elementary schools. Project-based collaborative learning is effective in developing 21st-century student character but requires ongoing strategies to optimally foster student initiative